The Effect of Traditional Games on the Physical Fitness of Students at Elementary School - Amirul Mukminin; Moch. Fahmi Abdulaziz (Universitas Negeri Semarang, 2026)
This research was motivated by children's preference for screen-based games that involve minimal physical activity over games that involve direct physical movement. This condition has contributed to a decline in the physical fitness levels of elementary school aged children. This study aims to assess the effect of traditional games on the physical health of sixth-grade students at Wates 02 Public Elementary School in Semarang City. A one-group pretest-posttest pre-experimental design was employed in a quantitative study. 28 sixth-grade pupils that were chosen using a saturation sample technique made up the research subjects. The Indonesian Physical Fitness Test (TKJI) was employed as the research instrument for ages 10 to 12 years. The data were examined descriptively and inferentially using normality, homogeneity, Wilcoxon, and r-square tests. The average physical fitness score of pupils increased from 15.29 in the pretest to 21.89 in the posttest, according to the results. The results of the Wilcoxon test indicated a significant difference between the pretest and posttest results following the installation of traditional games, with a significance value of 0.000 (p < 0.05). Furthermore, the outcomes of the R-squared test suggested that traditional games enhanced students' physical fitness by 50.4%. Based on these results, it can be claimed that the installation of traditional games has a major influence on boosting the physical fitness of sixth-grade students at Wates 02 Public Elementary School in Semarang City.